Ensemble neural network approach for accurate load forecasting in a power system - Siwek, Krzysztof; Osowski, Stanisław; Szupiluk, Ryszard (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents an improved method for 1?24 hours load forecasting in the power system, integrating and combining different neural forecasting results by an ensemble system. We will integrate the results of partial predictions made by three solutions, out of which one relies on a multilayer perceptron and two others on self-organizing networks of the competitive type. As the expert system we will apply different integration methods: simple averaging, SVD based weighted averaging, principal component analysis and blind source separation.
Keywords: neural networks; blind source separation; ensemble of predictors; load forecasting